First Approval of Adagrasib for the Treatment of Non-Small Cell Lung Cancer Harboring a KRASG12C Mutation - De, Surya K. (Current Medicinal Chemistry, 2024)
Adagrasib is an orally bioavailable, highly selective, small-molecule, irreversible covalent inhibitor of KRASG12C&. It was approved by the US FDA on December 12, 2022, for patients with tumors harboring the KRASG12C& mutation in locally advanced or metastatic non-small cell lung cancer (NSCLC). Herein, synthesis, dosage and administration, mechanism of action, pharmacokinetics, pharmacodynamics, and adverse events of adagrasib are described.
Keywords: KRAS mutation